Administrative Capacity in the Implementation of Digital Population Administration Services: A Literature Review of the KNG Program in Surabaya City Government - Dimas Rahmatullah; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
Digital transformation has become a central agenda in local governments seeking to improve the effectiveness, accessibility, and reliability of public service delivery, particularly in population administration services that constitute the legal foundation of citizenship. In Indonesia, the Surabaya City Government has implemented the Klampid New Generation (KNG) program as an integrated digital platform for population administration services, aiming to streamline civil registration processes, enhance service quality, and expand citizen access. Despite its technological ambition, the implementation of digital population administration services continues to face persistent challenges related to administrative capacity, especially at the municipal level where services are operationalized and directly experienced by citizens. This issue raises an urgent academic and practical question regarding how administrative capacity shapes the performance and sustainability of digital public services within the broader digital government transformation. This article aims to synthesize and critically evaluate the existing scholarly literature on administrative capacity in the implementation of digital population administration services, with analytical relevance to the KNG program in Surabaya City Government. Employing an integrative literature review design, the study systematically examines peer-reviewed journal articles published between 2021 and 2025, retrieved from Scopus, DOAJ, Google Scholar, and SINTA databases. Articles were selected based on predefined inclusion and exclusion criteria and analyzed using thematic and conceptual synthesis techniques. The review identifies key dimensions of administrative capacity that consistently influence digital service implementation, including institutional and organizational arrangements, human resource competence, technological and infrastructural readiness, regulatory and procedural alignment, inter-organizational coordination, and the role of street-level bureaucrats in frontline service delivery.